INFORMATION ON THE ETHNOGRAPHY OF THE POPULATION OF THE SOUTHERN REGIONS OF UZBEKISTAN IN THE WORKS OF RUSSIAN ORIENTALISTS (International Conference on Modern Science and Scientific Studies, 2025)
This article studies the ethnic composition of southern Uzbekistan, in particular the Kashkadarya and Surkhandarya oases, in the second half of the 19th century and the beginning of the 20th century from the perspective of historical migrations, genealogical structures, and political and social factors.